#### Answer

1

#### Work Step by Step

Using order of operations, first solve numerator and denominator separately, then simplify the fraction.
$\frac{-2 - 4^{2}}{3(-6)} = \frac{-2 - 16}{3(-6)} = \frac{-18}{3(-6)} = \frac{-18}{-18} = 1$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.